Christologie: Die spanningsvolle verhouding "Verkondiger - Verkondigde" by Rudolf Bultmann en Walter Schmithals - Boshoff, P. B. (Hervormde teologiese studies, 1993)
Christology - Rudolf Bultmann and Walter Schmithals on the relationship ‘Proclaimer - Proclaimed’ In the New Testament, Christology can be regarded as the reflection on the relationship between the ‘Proclaimer’ and the ‘Proclaimed’. This reflection deals with the existence of two traditions in early Christianity, namely the kerygmatic and the historical. The article, the first of three, shows how Rudolf Bultmann formulated the relationship between these two traditions . Walter Schmithals elaborated on Bultmann’s viewpoint. Both guard against the historical Jesus tradition supplanting the kerygmatic tradition based on the crucified and resurrected Christ.